Case Report of Mannose-Binding Lectin (MBL) Deficiency and Postoperative Sepsis and Coagulopathy in a Patient Following Total Pancreatectomy for Chronic Pancreatitis - Chung, Wen Yuan; Eltweri, Amar M; Gravante, Gianpiero; Arshad, Ali; Pollard, Cristina A; Metcalfe, Matthew S; Dennison, Ashley R (JOP. Journal of the Pancreas, 2014)
Context Complement plays a central role against infection and coordinates the activity of coagulation and fibrinolysis. In this report we present a patient that underwent total pancreatectomy experienced sepsis, coagulopathy and bleeding that endangered the postoperative course. Case report A sixty-five-year-old woman underwent total pancreatectomy for intractable pain without islet transplant, this patient was diagnosed as AP and MBL deficient from a blood test performed preoperatively. On the postoperative course she experienced severe haemorrhages and sepsis for 3 weeks postoperatively. An analysis of serial perioperative serum samples conducted which showed further depletion of the alternate and MBL complement pathway without restoration to baseline levels. Conclusion This is the first reported case of alternative and mannose-binding lectin pathways depletion associated with major postoperative bleeding and sepsis following pancreatic surgery. Future research should examine the relationship between complement pathways activity and postoperative complications in order to possibly introduce it as a preoperative screening and possible replacement therapy prior to any major surgical intervention. Image: Concentration of TAP, IL-1, IL-6, and IL-8 in MBL deficient patient.